PENERAPAN SISTEM INFORMASI AKUNTANSI ATAS SIKLUS PENDAPATAN PADA PT. PLN (PERSERO) RAYON SAMARINDA SEBERANG - Muhyar, Edy Muhyar (EKONOMIA, 2019)
Edy Muhyar, Faculty of Economics, University August 17, 1945 Samarinda, Application of Accounting Information Systems for the Revenue Cycle at PT. PLN (Persero) Samarinda Seberang Rayon, under the guidance of Mrs. Mardiana and Mrs. Camelia Verahastuti.The accounting information system implemented at PT. PLN (Persero) Rayon Samarinda Seberang as well as in general but based on observations of the accounting information system has not gone well, this is due to the lack of skills (skills) possessed in using customer data processing applications, so that learning and training is needed. In addition, in carrying out the task there is a dual function, so the possibility of an indication of detrimental to PT. PLN (Persero) Samarinda Seberang Rayon. The author chose PT. PLN (Persero) Rayon Samarinda Seberang as the object of research because it is interested in the problem of accounting information systems for the income cycle. The purpose of this study was to determine the application of accounting information systems for the income cycle carried out at PT. PLN (Persero) Samarinda Seberang Rayon based on internal control components.The analytical tool used in this study is comparing the components of the internal control system and flowchart according to the theory with the internal control system applied to PT. PLN (Persero) Samarinda Seberang Rayon and questionnaire.After going through the research phase, analysis and discussion is known that the internal control system applied by PT. PLN (Persero) Rayon Samarinda Seberang is in accordance with the components of internal control, this is seen from the results of the study which obtained 83.2% which means it is very suitable. Thus, the proposed hypothesis is that the application of accounting information systems to the income cycle at PT. PLN (Persero) Samarinda Seberang Rayon, not in accordance with the components of internal control rejected) .